Pengaruh Pemberian Insentif dan Bonus Terhadap Tingkat Produktivitas Kerja Karyawan pada PT. Bank Pembiayaan Rakyat Syariah Bhakti Sumekar Sumenep - Siti Qamariyah; Fadllan Fadllan (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2017)
In the increasingly tight globalization of competition within the company. Where the Company needs to pay special attention to Human Resources. In the company needs a stimulus that is in the form of incentives and bonuses. With these stimuli they can be motivated to work so that their needs are met, and generate high productivity   for a company / organization. This study aims: first, To determine whether the incentives and bonuses have an effect on the level   of employee productivity at PT. BPRS Bhakti sumekar. Second, To know how much influence the giving of incentives and bonus to level  employee work productivity at PT. BPRS Bhakti sumekar. The type of research used in this study using a quantitative approach with multiple linear regression analysis techniques. The type of data used is the primary data obtained through questionnaires and secondary data obtained from company data (documents). Respondents are employees of PT. Bhakti Sumekar BPRS which totals 36 employees, with sampling technique using saturated samples. From result of research indicate that there is influence of incentive and bonus to level of work productivity of employees at PT. BPRS Bhakti sumekar. Based on simultaneous test results show that the value of F arithmetic > F table ( 11,191 > 4,13)  with significant 0.000 <0.05. The t test results are partially incentive variables, where t arithmetic <t table ( 3.355 > 1.690), and bonus variables where t arithmetic > t table ( 2.173 > 1.690), indicate that the incentive variable and bonus variable have the same effect significant to work productivity of employees at PT. BPRS Bhakti Sumekar . The test results of R 2 of 40.4%. From the results of multiple regression analysis variable X 1 (incentives) which has the greatest influence on employee productivity of 0 , 439(34.4%).